2016
DOI: 10.18632/oncotarget.9215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Notch1 by Pim kinases promotes oncogenic signaling in breast and prostate cancer cells

Abstract: Tumorigenesis is a multistep process involving co-operation between several deregulated oncoproteins. In this study, we unravel previously unrecognized interactions and crosstalk between Pim kinases and the Notch signaling pathway, with implications for both breast and prostate cancer. We identify Notch1 and Notch3, but not Notch2, as novel Pim substrates and demonstrate that for Notch1, the serine residue 2152 is phosphorylated by all three Pim family kinases. This target site is located in the second nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 59 publications
2
84
0
Order By: Relevance
“…28 Interestingly, phosphorylation of Notch-1 by Pim (proviral insertion in murine) kinases promoted oncogenic signaling in prostate cancer cells. 29 Recently, one study identified that inhibition of Notch pathway arrested PTEN-deficient advanced prostate cancer via enhancing p27-driven cellular senescence. 30 Studies investigated the function of Notch signaling pathway in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…28 Interestingly, phosphorylation of Notch-1 by Pim (proviral insertion in murine) kinases promoted oncogenic signaling in prostate cancer cells. 29 Recently, one study identified that inhibition of Notch pathway arrested PTEN-deficient advanced prostate cancer via enhancing p27-driven cellular senescence. 30 Studies investigated the function of Notch signaling pathway in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NDRG1 expression in HepG2 cells leads to increased membrane-localized beta-catenin, which promotes a less migratory phenotype and greater cell-cell contact 45 . In light of these findings, and given the previously demonstrated ability of PIM1 to promote cell migration and invasion 58,59 , we investigated the effect of NDRG1 phosphorylation on the migration and invasion of prostate cancer cells. To examine migration, we exogenously expressed WT NDRG1 or NDRG1 S330A in PIM1 overexpressing LNCaP and VCaP cells (Suppl.…”
Section: Ndrg1 Ps330 Is Associated With Inhibition Of Prostate Cancermentioning
confidence: 99%
“…Previous reports have proposed a number of potential kinases which may be involved in NICD phosphorylation and turnover, including CyclinC:CDK8 [36], CyclinC:CDKs [63], PKC [66], PIM [67] and GSK3b [35,37] kinases. The MRC-PPU Kinase Profiling Inhibitor Database (http://www.kinase-screen.mrc.ac.uk/kinaseinhibitors) (University of Dundee) indicates that, at the concentrations used in our assays, Roscovitine, in particular, is a potent inhibitor of CDK2, but a very weak inhibitor of CK1, GSK3b and more than 50 other kinases tested.…”
Section: Cyclin-dependent Kinase (Cdk) 1 and 2 Phosphorylate Nicd In mentioning
confidence: 99%